2022
DOI: 10.1186/s12864-022-08647-w
|View full text |Cite|
|
Sign up to set email alerts
|

The extensive transgenerational transcriptomic effects of ocean acidification on the olfactory epithelium of a marine fish are associated with a better viral resistance

Abstract: Background Progressive CO2-induced ocean acidification (OA) impacts marine life in ways that are difficult to predict but are likely to become exacerbated over generations. Although marine fishes can balance acid–base homeostasis efficiently, indirect ionic regulation that alter neurosensory systems can result in behavioural abnormalities. In marine invertebrates, OA can also affect immune system function, but whether this is the case in marine fishes is not fully understood. Farmed fish are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 136 publications
0
16
0
Order By: Relevance
“…While neural plasticity could facilitate increased flexibility to environmental changes (Ebbesson & Braithwaite, 2012), it could result in behavioural alterations that have been observed in fish exposed to OA conditions (Schunter et al, 2019). Increased GABAergic signaling is a commonly observed within-generation response to elevated CO2 in A. polyacanthus (Schunter et al, 2018) and a similar increase in neural signaling pathways was found in the olfactory epithelium of European seabass (D. labrax) even after prolonged transgenerational OA exposure for two generations (Cohen-Rengifo et al 2022). The restoration of OA induced changes in neural signaling processes with previous parental exposure to elevated CO2 could indicate elevated intergenerational plasticity of A. polyacanthus.…”
Section: Discussionmentioning
confidence: 94%
“…While neural plasticity could facilitate increased flexibility to environmental changes (Ebbesson & Braithwaite, 2012), it could result in behavioural alterations that have been observed in fish exposed to OA conditions (Schunter et al, 2019). Increased GABAergic signaling is a commonly observed within-generation response to elevated CO2 in A. polyacanthus (Schunter et al, 2018) and a similar increase in neural signaling pathways was found in the olfactory epithelium of European seabass (D. labrax) even after prolonged transgenerational OA exposure for two generations (Cohen-Rengifo et al 2022). The restoration of OA induced changes in neural signaling processes with previous parental exposure to elevated CO2 could indicate elevated intergenerational plasticity of A. polyacanthus.…”
Section: Discussionmentioning
confidence: 94%
“…From the extracted RNA samples, five from each group were selected based on the quality of the RNA and they were sent for transcriptome analysis via RNA sequencing at GenomiX (MGX, Montpellier, France) following the procedure described by Cohen-Rengifo et al 66 Total RNA was quantified on Fragment Analyzer (Agilent Technologies, Santa Clara, CA, USA) using the standard sensitivity RNA kit (DNF-471-0500). Libraries were constructed using Stranded mRNA Prep Ligation kit (Illumina, San Diego, CA,USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study just demonstrated that exposure to chemicals in plastic products resulted in epigenetic changes in marine fish, which was passed on to both their offspring (F1) and the subsequent generation of marine fish (F2) (Cohen-Rengifo et al, 2022). Interestingly, this epigenetic change led to greater viral resistance to the chemicals (along with changes to their metabolism and scent detection).…”
Section: The Neuroscience Of Transgenerational Traumamentioning
confidence: 99%